(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Compare the analgesic effect in labor of three electric syringe settings for patient -controlled epidural anesthesia (PCEA). Research method: Cross-sectional descriptive method, conducted from October 2024 to September 2025, at Thanh Hoa Obstetrics and Gynecology Hospital. 90 primiparous mothers were divided into three groups: Group A: Bolus injection of 3ml of analgesic mixture, lock time of 6 minutes. Group B: Bolus injection of 6ml of analgesic mixture, lock time of 12 minutes. Group C: Bolus injection of 9ml of analgesic mixture, lock time of 18 minutes. All 3 groups have a continuous maintenance dose of 3ml/h, maximum dose of 80ml/4h. Anesthetics used are: levobupivacaine 0.1% and fentanyl 2µg/ml. Results: The onset of analgesic effect in group A was slower than in groups B and C. The rate of using rescue analgesic doses in group C was the lowest. The pain score (VAS) maintained throughout the analgesic process during labor was less than 4 in all stages of labor in all 3 groups. Group C had a higher rate of motor inhibition than the other two groups. 100% of the mothers in all 3 groups were satisfied and very satisfied with the pain relief during labor. Conclusion: The regimen for setting the electric syringe pump in PCEA (levobupivacaine 0.1% and fentanyl 2µg/ml), which has good analgesic effect and does not affect the mother’s movement is: Bolus injection of 6ml each time the mother presses the control button, lock time of 12 minutes, base dose of 3ml/h And the bolus injection group: bolus volume 9 ml, lockout interval 18 minutes, basal infusion rate 3 ml/h